Pharmacokinetics and metabolism of artemisinin (ART) in Plasmodium yoelii: ART-heme adduct as a potential biomarker for its resistance - Shanshan Du; Kun Xu; Zhaohua Liu; Jie Xing (International Journal for Parasitology: Drugs and Drug Resistance)
Background: Plasmodium falciparum in Southeast Asia and Africa is developing resistance to the antimalarial drug artemisinin (ART). In this study, the metabolite of ART in P. yoelii parasites was evaluated as a potential biomarker for its antimalarial activity as well as its resistance. Methods: The induced strain of P. yoelii (iPy) was first established after long-time pressure of ART in P. yoelii (Py)-infected mice. The metabolic and pharmacokinetic profiles of ART were then studied in both P. yoelii parasites and infected mice. The pharmacokinetic-pharmacodynamic behaviors of ART in two strains of P. yoelii (Py and iPy) were compared. The pharmacokinetic parameters (e.g., AUC and Cmax) of ART metabolite in parasites were normalized by infected RBC (iRBC) burden. Results: Lower antimalarial activity was found for ART against iPy than Py, in terms of the 90 % growth inhibitory dose (ED90, 2.9-fold). In contrast with Py, mice infected with iPy could survive for at least 28 days. When ART was orally given to (i)Py-infected mice, ART was detected in parasites as ART-heme adduct. The plasma clearance of ART was not affected by (i)Py-infection, and higher plasma clearance of ART (by 3-4-fold) was found after multiple doses. After being normalized by iRBC, the exposure of ART-heme in P. yoelii parasites was dose-dependent, and its maximum concentration (Cmax) was reached at 3–5 h. Compared with Py parasites, lower iRBC-normalized exposure of ART-heme (AUC0-t, normalized) was found in iPy parasites (61.1 % of Py parasites) after an oral dose of ART to infected mice. Conclusions: Plasma ART concentration merely reflected drug exposure in the host. ART-heme adduct was the major metabolite for ART in P. yoelii parasites, and it could be a potential biomarker for the antimalarial activity of ART as well as its resistance.